ROLE OF QĀDĪ’S IN THE ISLAMIC INSTITUTIONS - A’zam M. Qambarov (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
The article is based on most recent accomplishments, conclusions and methods in World Islamic and historical sciences. The historical-comparative method was applied to study the sources including various manuscripts of “Ḥanafī Law” and many other sources written in Arabic that are available in the Fund of Manuscripts of the Institute of Oriental Studies under Academy of Sciences of the Republic of Uzbekistan.